The Influence of Nurse Motivation on the Implementation of SBAR Communication during Handover - Rosadatin Chandrawati; Puguh Widiyanto; Sri Hananto Ponco Nugroho (Media Keperawatan Indonesia)
SBAR communication is an effective tool that helps nurses organize their thoughts, facilitates clear communication, and enhances their communication skills. Motivation and work commitment are critical factors that influence patient safety in hospital settings. This study aims to examine the relationship between nurse motivation and the implementation of SBAR communication during handovers in inpatient wards. A descriptive cross-sectional design was employed, involving a single observation and simultaneous measurement of 63 nurse respondents. The results demonstrated a significant positive correlation between nurse motivation in achieving patient safety goals and the use of SBAR communication during handovers, as indicated by a p-value of 0.008 (<0.05) and a correlation coefficient (r) of 0.331. These findings suggest that higher nurse motivation is associated with better communication practices in patient handovers.